2019
DOI: 10.3750/aiep/02546
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of tide pool use by a viviparous elasmobranch as a parturition site

Abstract: Wosnick N., Rios R.M., Rincon G., Nunes J.L.S. 2019. Evidence of tide pool use by a viviparous elasmobranch as a parturition site. Acta Ichthyol. Piscat. 49 (2): 189-193.Abstract. Despite the frequent occurrence of elasmobranchs in surf zones, the use of tidal pools by these animals is unknown, with only one incidental observation reported in the literature. Here we present a possible birth observation in a tide pool for the shortnose guitarfish, Zapteryx brevirostris (Müller et Henle, 1841). We discuss this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Regarding growth, wild specimens of Z. brevirostris evaluated in other studies, showed a negative allometric growth ( b < 3), which means that the species invests more in its growth in length than in mass, which agrees with the results found in this study (Pasquino et al ., 2016). Size at birth was also in accordance with literature, with values among 13 cm, as expected for Z. brevirostris , which neonates' ranges from 13 to 16 cm in length (Wosnick, Rios, et al ., 2019; Caltabellotta et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding growth, wild specimens of Z. brevirostris evaluated in other studies, showed a negative allometric growth ( b < 3), which means that the species invests more in its growth in length than in mass, which agrees with the results found in this study (Pasquino et al ., 2016). Size at birth was also in accordance with literature, with values among 13 cm, as expected for Z. brevirostris , which neonates' ranges from 13 to 16 cm in length (Wosnick, Rios, et al ., 2019; Caltabellotta et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As most shark and ray species are ectotherms, ambient temperatures directly influence metabolic and physiological processes and are therefore considered one of the main drivers of their distribution, movement and habitat selection (Bernal et al, 2012; Morrissey & Gruber, 1993; Schlaff et al, 2014). Elasmobranchs select shallow coastal waters due to their higher temperature to increase digestion rates (Papastamatiou et al, 2015), (embryonic) growth rates and to shorten gestation times (Jirik & Lowe, 2012; Wosnick et al, 2019). Our review shows that sharks and rays might select intertidal habitats for thermoregulatory purposes, as intertidal water temperatures are often higher than adjacent subtidal waters (Bridges, 1993; Hernández et al, 2002).…”
Section: Intertidal Habitat Use By Sharks and Raysmentioning
confidence: 99%
“…Smith (2005) described that leopard sharks mate on intertidal soft‐bottom flats in California. Shortnose guitarfish potentially use tide pools for parturition (Wosnick et al, 2019). This limited evidence suggests that some shark and ray species use the intertidal for reproductive purposes, to maximize mating success, maximize gestational development and for increased survival of egg cases.…”
Section: Intertidal Habitat Use By Sharks and Raysmentioning
confidence: 99%